High expression of P-selectin induces neutrophil extracellular traps via the PSGL-1/Syk/Ca2+/PAD4 pathway to exacerbate acute pancreatitis - Xu, Qi; Shi, Ming; Ding, Lu; Xia, Yu; Luo, Liang; Lu, Xiaofang; Zhang, Xiaoying; Deng, David Y. B. (Frontiers in Immunology, 2023)
Background: Excessive neutrophil extracellular traps (NETs) is involved in the progression of acute pancreatitis (AP) but the mechanisms controlling NETs formation in AP are not fully understood. Therefore, our study sought to investigate the mechanism of the highly expressed P-selectin stimulating the formation of NETs in AP. Methods: NETs formation was detected by flow cytometry, immunofluorescence staining, and cf-DNA and MPO-DNA complexes were measured as biomarkers of NETs formation. Neutrophils treated with P-selectin and pharmacological inhibitors were examined by western blot, immunofluorescence staining and flow cytometry. Mouse model of AP was established by caerulein and the effect of inhibiting P-selectin by PSI-697 on the level of NETs and PAD4 in pancreatic tissue was observed. The severity of AP was evaluated by histopathological score and the detection of serum amylase and lipase. Results: Patients with AP had elevated levels of NETs and P-selectin compared with healthy volunteers. Stimulation of P-selectin up-regulated the expression of PSGL-1, increased the phosphorylation of Syk, mediated intracellular calcium signal and led to the activation and expression of PAD4, which modulated NETs formation in neutrophils.Pretreament with PSI-697 blunted NETs formation and PAD4 expression in the pancreatic tissue, and ameliorated the severity of AP in mice. Conclusions: Taken together, these results suggest that P-